2012
DOI: 10.1097/iae.0b013e318232c34c
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Analgesia With Ropivacaine for Pars Plana Vitrectomy

Abstract: The study highlights the benefit of the concept of preemptive analgesia in general: the peribulbar injection of 5 mL of 0.75% ropivacaine before surgery provides a substantial benefit in terms of analgesic demand and postoperative discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Two review authors (AL and SS) independently scanned the identified references and excluded references which were not relevant to the scope of this review. We identified six studies which were potentially relevant to the interventional question posed (Celiker 2014;Kristin 2001;Lai 2005;Mahajan 2013;Schönfeld 2012;Tan 2005). On closer review none of these six studies met the selection criteria.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Two review authors (AL and SS) independently scanned the identified references and excluded references which were not relevant to the scope of this review. We identified six studies which were potentially relevant to the interventional question posed (Celiker 2014;Kristin 2001;Lai 2005;Mahajan 2013;Schönfeld 2012;Tan 2005). On closer review none of these six studies met the selection criteria.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Additionally, various methods of preventive analgesia (PA) for PPV, such as regional techniques [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and intravenous techniques with preoperative infusion of COX-3 inhibitors (paracetamol, metamizole) [ 21 , 22 ], were shown to provide adequate postoperative analgesia [ 17 ], with a fall in the rate of main adverse events [ 12 , 15 , 23 ] within the mechanism of a reduction in demand for IO.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Fekrat S et al [49], 56% of patients complained of some eye pain after VRS, whereas 48% requested an analgesic within 5 hours after surgery, and 27% percent of patients required OA. Schönfeld CL et al [25] found GA with PBB using 0.75% ropivacaine with 75 IU of hyaluronidase in a volume of 5 ml superior for the prevention of PIPP compared to a volume of 1 or 3 ml. Sixty percent of patients receiving 5 ml experienced no PIPP after one hour of VRS in this study.…”
Section: Postoperative Intolerable Pain Perception (Pipp)mentioning
confidence: 99%
“…Attempts have been made to reduce the dose of intraoperative OA with different techniques of preventive analgesia for VRS. Reduction in the intravenous dose of OA administered intraoperatively with a combination of GA and regional techniques, including preoperative peribulbar block (PBB) [22,23,24,25,26], retrobulbar block (RBB) [27,28], subtendon block [29,30] and topical anaesthesia (TA) [31] have been proven to provide adequate analgesia postoperatively [28], with reduced incidence of OCR [32] and PONV [23,26], despite potential side effects [3].…”
Section: Introductionmentioning
confidence: 99%